2021
DOI: 10.1002/nop2.974
|View full text |Cite
|
Sign up to set email alerts
|

The use of oral and enteral tube‐fed arginine supplementation in pressure injury care: A systematic review and meta‐analysis

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Moreover, it has been reported that NO promotes blood flow (Hambrecht et al 2000 ) and improves male sexual function (Barassi et al 2017 ), indicating NO’s vasodilatory activity. NO has also been reported to elevate growth hormone activity (Chromiak and Antonio 2002 ; Lind 2004 ; Visek 1986 ) and enhance wound healing (Cheshmeh et al 2022 ; Lind 2004 ; Visek 1986 ). Consequently, NO is occasionally used for improving athletic performance (Shao and Hathcock 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been reported that NO promotes blood flow (Hambrecht et al 2000 ) and improves male sexual function (Barassi et al 2017 ), indicating NO’s vasodilatory activity. NO has also been reported to elevate growth hormone activity (Chromiak and Antonio 2002 ; Lind 2004 ; Visek 1986 ) and enhance wound healing (Cheshmeh et al 2022 ; Lind 2004 ; Visek 1986 ). Consequently, NO is occasionally used for improving athletic performance (Shao and Hathcock 2008 ).…”
Section: Introductionmentioning
confidence: 99%